[Rezension von: Repschinski, Boris, 1962-, The controversy stories in the Gospel of Matthew : their redaction, form und relevance for the relationship between the Matthean community and formative Judaism] - Hunter, Alastair G. (The journal of theological studies, 2004)
The Controversy Stories in the Gospel of Matthew. Their Redaction, Form and Relevance for the Relationship Between the Matthean Community and Formative Judaism. Boris Repschinski Pp. 373 (Forschungen zur Religion und Literatur des Alten und Neuen Testaments, 189.) Göttingen Vandenhoeck & Ruprecht 2000 3 525 53873 1. DM 128.